Analisis Kinerja Keuangan KUD Werdhi Mendala Di Desa Batubulan Kecamatan Sukawati Kabupaten Gianyar - WAHYUNINGSIH, NI MADE; RANTAU, I KETUT; YUDHARI, I DEWA AYU SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.1, Januari 2018DO - 10.24843/JAA.2018.v07.i01.p14, 2018)
The Financial Performance Analysis of Rural Cooperative of Werdhi Mendala In Batubulan Village Sukawati Sub-District of Gianyar Regency KUD or rural cooperative is expected to be able to realize economic democracy in the efforts to develop cooperatives into an independent people's economic institutions. The financial statements are an important tool for obtaining information related to the financial condition and results of cooperative activities. The objectives of the research are to determine (1) the ability of KUD to fulfill its short term financial obligation assessed from the liquidity ratio, (2) how far is the KUD assets financed by its debt assessed from the solvency ratio, (3) how effective the KUD in using its funding source assessed from the activity ratio and (4) the ability of KUD to obtain the Return on Investment assessed by the profitability ratio. Types of data used in the study are qualitative data and quantitative data with financial ratio analysis as a method of data analysis in the research. Data Sources of the study are primary and secondary data. The key informants were the Manager and Finance Department of KUD Werdhi Mendala. Data analysis method used is financial ratio analysis. Financial ratios used are the ratio of liquidity, solvency ratio, activity ratio and profitability ratio.The result of ratio analysis during 2011-2015 shows that liquidity ratio at current ratio and quick ratio is said to be very inadequate. The solvency ratio in total debt to equity ratio and total debt to total asset are said to be very inadequate. The ratio of activity to total assets turnover is not good and receivable turnover is said to be very inadequate. Profitability ratio on net profit margin is said to be quite capable, return of investment / ROI is said to be very inadequate and return of equity / ROE (Rentability of Own Capital) is said to be quite capable.